Post-Divorce Maintenance in Contemporary Islamic Family Law: An Empirical Study of Judges' Considerations at the East Jakarta Religious Court - Abdul Aziz; Iqbal Subhan Nugraha; Lukman Hakim (Legitima : Jurnal Hukum Keluarga Islam, 2024)
Purpose – This research aims to analyze the application of post-divorce maintenance in contemporary Islamic family law, focusing on an empirical study of judges' considerations at the East Jakarta Religious Court. This research will explore how judges consider the obligations of nafkah madhiyah, mut'ah, and iddah in divorce verdicts, as well as the legal and social implications for women involved in the process. Methods – This research uses a field research method with a case study approach with a focus on contemporary problems in family law. Data was collected through in-depth interviews with judges, clerks handling divorce cases, substitute clerks handling divorce cases, and analysis of relevant legal documents. Findings – The findings of this study indicate that the obligation to provide maintenance in the East Jakarta Religious Court serves as a protection of women's rights and as part of efforts to achieve social and gender justice in the contemporary era. The results of this study indicate that the application of financial provisions in Islamic law is essential to protect women's rights and reduce the potential economic hardship experienced after divorce. Research implications – Achieving equality and justice in gender relations requires reforms in legal policies and practices to be more responsive to women's needs, particularly in the context of divorce. This research makes a significant contribution to understanding the interaction between law, gender and social justice in society in an increasingly complex contemporary era. This research only focuses on cases in a particular region, so the results cannot be generalized to other contexts.